Combined adjustment of injection timing and compression ratio for an agricultural diesel engine fuelled with Nahar methyl ester. Issue 1 (31st December 2022) - Dash, Santosh Kumar; Lingfa, Pradip; Barik, Debabrata
Abstract : This study investigates the effect of compression ratio (CR: 16, 17, standard 17.5, 18) and injection timing (IT: 21°CA, standard 23, 25°CA) of a single cylinder direct injection diesel engine having power output 3.5 kW at rated speed 1500 rpm fuelled by an optimal Nahar methyl ester blend (NME40). For NME40/CR18, the BTE is improved by 1.09% and EGT is lowered by 2.98% compared to NME40 at standard engine settings, at full load. The HC, CO, and smoke emission decreased for NME40/CR18 by about 15.38%, 21.5%, and 0.5% compared to NME40 at standard setting, whereas it is reduced by 25.45%, 23.73%, and 3.4% compared to diesel respectively at full load. At full load, the NOx emission for NME40/CR18 lowered by 4.73% compared to diesel. Combustion analysis reveals that higher CR has positive impact on cylinder peak pressure. Lower ID observed for higher CR and retarded IT operation.